Thermally reconfigurable Janus droplets with nematic liquid crystalline and isotropic perfluorocarbon oil compartments. Issue 12 (28th February 2019) - Wang, Xin; Zhou, Ye; Kim, Young-Ki; Tsuei, Michael; Yang, Yu; de Pablo, Juan J.; Abbott, Nicholas L.
Abstract : We report formation of Janus droplets with coexisting liquid crystalline and isotropic compartments, stable spherical shapes, and widely tunable internal morphologies. Abstract : We report that mixtures of perfluorocarbon oils and hydrocarbon mesogens can be used to prepare multi-compartment (Janus) emulsion drops comprising coexisting nematic liquid crystalline (LC) and isotropic oil phases. The droplets exhibit stable spherical shapes with internal Janus-type morphologies that can be tuned widely through changes in temperature or adsorbates. In particular, we observe evidence of preferential adsorption of hydrocarbon or fluorocarbon surfactants on the interfaces of nematic versus isotropic domains, respectively, providing added control over the droplet structure. Comparisons of experiments and numerical simulations using a Landau–de Gennes continuum model provide insight into the relative importance of the LC elasticity and orientational-dependent interfacial energies on droplet morphologies and properties. We show that the hierarchical organization of the LC compartments generates optical properties and responsiveness not found in emulsions of isotropic oils.